Changing home care aides: Differences between family and non-family care in California Medicaid home and community-based services. Issue 1 (2nd January 2020) - Ko, Michelle; Newcomer, Robert J.; Bindman, Andrew B.; Kang, Taewoon; Hulett, Denis; Spetz, Joanne
ABSTRACT: In California Medicaid home-and-community-based services (HCBS), recipients' family members receive payment as home care aides (HCAs). We analyzed data on first-time HCBS recipients to examine factors associated with the likelihood of switching HCAs within the first year of services. Those with family HCAs were less than half as likely to change than those with non-family HCAs and racial/ethnic minorities with non-family HCAs had the highest switching rates. Lower wages and local unemployment were associated with switching of non-family HCAs but not family HCAs. Policymakers can foster continuity of home care by paying family members for home care and raising worker wages.